2011
DOI: 10.1113/jphysiol.2011.208066
|View full text |Cite
|
Sign up to set email alerts
|

GluA4 is indispensable for driving fast neurotransmission across a high‐fidelity central synapse

Abstract: Non-technical summary Localization of sound sources in the azimuth, which makes use of interaural differences in timing and/or intensity of acoustic signals, is of vital importance for most mammals. Using the small differences in time of arrival and/or intensity at the two ears requires that propagation of electric pulses in the auditory system be temporally precise. In this study, we found that elimination of GluA4, a protein particularly abundant in auditory cells, significantly impairs their ability to fait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 67 publications
6
63
1
Order By: Relevance
“…AMPA receptors in bushy cells are composed of GluA3 and 4 isoforms as flop splice variants (Gardner et al 2001;Wang et al 1998). In targets of bushy cells it has been demonstrated that GluA4, but not GluA3, is crucial and that GluA2 can substitute for GluA3 but not for GluA4 (Yang et al 2011). The finding that mEPSCs have similar shapes suggests that the subunit composition of AMPA receptors is similar in Otoferlin mutant and control mice.…”
Section: Discussionmentioning
confidence: 58%
“…AMPA receptors in bushy cells are composed of GluA3 and 4 isoforms as flop splice variants (Gardner et al 2001;Wang et al 1998). In targets of bushy cells it has been demonstrated that GluA4, but not GluA3, is crucial and that GluA2 can substitute for GluA3 but not for GluA4 (Yang et al 2011). The finding that mEPSCs have similar shapes suggests that the subunit composition of AMPA receptors is similar in Otoferlin mutant and control mice.…”
Section: Discussionmentioning
confidence: 58%
“…Since the CN is the first central station that encodes the timing of auditory signaling (Trussell, 1999), it is likely that timing is deficient in the absence of GluA3. A recent study by Yang et al (2011) showed that the lack of GluA4 affects ABR amplitudes and latencies of P3 and P4. Together with our findings, these observations suggest that GluA3 and GluA4 are each necessary for normal auditory signaling within defined synapses of the auditory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Together with our findings, these observations suggest that GluA3 and GluA4 are each necessary for normal auditory signaling within defined synapses of the auditory pathway. Since in the MNTB, GluA4 is essential for fast synaptic transmission (Yang et al, 2011), it is likely that GluA3 plays a similar role in the CN. This is supported by our findings on increased latency of P2 (CN).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, AMPA receptors gate more rapidly due to increased use of the flop splice variant of GluR4 (Joshi et al, 2004; Koike-Tani et al, 2005). This shift in receptor subunit composition is critical for the rapid transmission typical of the calyx synapse, as deletion of GluR4 significantly slows the time course of AMPAR-type EPSCs, reduces the current amplitude, and exacerbates receptor desensitization (Yang et al, 2011b). Additionally, PSD-95 and Homer-1 may help to concentrate AMPA receptors within PSDs, further contributing to fast and precise neurotransmission (Hermida et al, 2010; Soria Van Hoeve et al, 2010).…”
Section: Development Of the Calyx Of Heldmentioning
confidence: 99%